Pendidikan Kesehatan tentang Anemia kepada Ibu Hamil - Safitri Safitri (Jurnal Abdimas Kesehatan (JAK), 2020)
AbstractAnemia is a major factor causing maternal morbidity and mortality in developing countries. According to the World Health Organization (WHO) the prevalence of anemia in pregnant women in developing countries is 51%. In Indonesia, based on the results of the 2018 Riskesdas survey, data on the proportion of anemia in pregnant women increased from 37.1% (2013) to 48.9% (2018). Likewise, the Jambi City, in the Puskesmas Pakuan Baru there are still pregnant women who have anemia. Target outcomes expected are: there is an increased knowledge between before and after counseling. The method used is counseling. The results of dedication are an increase in knowledge in pregnant women as an effort to prevent and recognize high risk or complications of Anemia in early pregnancy.